2019
DOI: 10.1542/peds.2017-4111
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Drug-Drug Interaction Alerts Using a Multidimensional Approach

Abstract: OBJECTIVES: Excessive alerts are a common concern associated with clinical decision support systems that monitor drug-drug interactions (DDIs). To reduce the number of low-value interruptive DDI alerts at our hospital, we implemented an iterative, multidimensional quality improvement effort, which included an interdisciplinary advisory group, alert metrics, and measurement of perceived clinical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…and Daniels et al . reduced the number of alerts by ~ 50% 12,33 . Improvement in PPV was also demonstrated, i.a., by Eppenga et al ., increasing from 9.9% to 14.8% after introducing a contextualized DDI‐CDS 32,35 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…and Daniels et al . reduced the number of alerts by ~ 50% 12,33 . Improvement in PPV was also demonstrated, i.a., by Eppenga et al ., increasing from 9.9% to 14.8% after introducing a contextualized DDI‐CDS 32,35 .…”
Section: Discussionmentioning
confidence: 82%
“…In practice, however, such DDI alerts are frequently overridden as most alerts are considered to be irrelevant for specific patients. [9][10][11][12][13] Too many irrelevant alerts can lead to alert fatigue, 9,13-15 described as a "mental state being the result of too many irrelevant alerts consuming time and mental energy, which can cause important alerts to be ignored along with clinically unimportant ones." 16 Basic DDI-CDS systems have limited options for suppressing irrelevant DDI alerts, other than turning DDI alerts off for specific drug combinations.…”
Section: Articlementioning
confidence: 99%
“…A number of studies (n = 26) described optimization strategies, implemented as single-component interventions (Table 2). 15–40 Table 2 summarizes the various single-component optimization strategies used in the included studies, highlighting the stage of the ePrescribing process being optimized and the overall reported effectiveness of the intervention on the primary outcome.…”
Section: Resultsmentioning
confidence: 99%
“…At the prescriber interface of ePrescribing systems, CDS, 17,[19][20][21]23,24 order sets, 25 alerts, 18,22 and a data dashboard 26 were all deployed as optimization strategies. Computerized decision support was often applied as an optimization strategy to aid the management of clinical conditions with standardized treatment algorithms amenable to decision support.…”
Section: Prescribingmentioning
confidence: 99%
“…Using examples from PDDI clinical decision support, an in situ qualitative study of prescribers’ interaction with electronic medication alerts showed that prescribers bypassed the alert and then searched for patient-specific data that they needed when alerts failed to provide contextual information ( Russ et al, 2012 ). Similarly, quality improvement projects have found that making PDDI alerts more appropriate to clinical context can improve alert acceptance ( Daniels et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%